article text Artikel Penentuan Harga Pokok Produk Metode Harga Pokok Pesanan Pada Percetakan Fahmi Gemurung: Penentuan Harga Pokok Produk Metode Harga Pokok Pesanan Pada Percetakan Fahmi Gemurung - Dian Fahriani; Diana Sharfina; Anindita Putri Novinda; Atika Muhfida Hanum; Reni Yusnita (Universitas Nahdlatul Ulama Sidoarjo, 2023)
Abstract This research is useful in order to be able to know the cost of the product and the ordering product price method at the Fahmi Gemurung Printing. Research that we apply using descriptive analysis. This evidence is presented using an interview process. This study presents that the cost of products made by Fahmi Gemurung Printing already uses the order principal method. The direction of this research is to find out the price of the product in each order and the total cost of each order and each unit. Characteristics of job order costing at Fahmi Gemurung Printing For special order production, each product unit needs to be calculated separately, and the expenses incurred during production can be divided into direct production costs and indirect production costs. Direct production costs consist of raw material costs and labor costs which are calculated based on realized costs. This order will obtain a price by calculating the orders that have been received divided by the total cost of production.